Dynamics and mechanisms of bioaccumulation and elimination of nonylphenol in zebrafish. (1st January 2023) - Peng, Cheng; Zhou, Shanqi; Zhang, Yinjie; Zhang, Hongchang; Zhang, Wei; Ling, Siyuan; Hu, Shuangqing
Abstract: Nonylphenol (NP) has been widely concerned for its endocrine disrupting effects. In this study, we investigated the accumulation and elimination of NP for the whole body and trunk of zebrafish ( Danio rerio ). The results show that the LC50 values of NP in zebrafish ranged from 474 μg·L −1 (24-h exposure) to 238 μg·L −1 (96-h exposure). Meanwhile, the NP concentrations in zebrafish during the depuration stage fitted the first-order kinetic model well, and the depuration rate constant (K2 ) was reduced from 0.412 d −1 to 0.2827 d −1 with higher NP. The half-life (t1/2 ) of NP was 1.75–2.45 d in the whole fish and 0.56–0.86 d in the trunk under low to high NP, respectively. Both the accumulation and elimination of NP in trunk were faster than those in whole fish, indicating the preferential transfer from viscera to muscle and rapidly diffusion in reverse. The bioconcentration factors (BCFSS ) of NP were 104–112 L·kg −1 in whole body and 76–104 L·kg −1 in trunk, respectively, suggesting that the muscle was a major position for NP storage. Graphical Abstract: ga1 Highlights: The LC50 values of NP ranged from 474 to 238 μg·L −1 during 96 h incubation. NP bioaccumulation in zebrafish was fast and mainly occurred at an early uptake stage. Accumulation and elimination of NP in trunk were both faster than that in whole fish. Muscle was a major storage part of NP in zebrafish. The BCFSS increased with exposure dose within a certain concentration range.